Submaximal oxygen deficit during incremental treadmill exercise in elite youth female handball players - Béres, B.; Györe, I.; Zsákai, A.; Dobronyi, T.; Bakonyi, P.; Szabó, T. (Sports, 2025)
Laboratory-based assessment of cardiorespiratory function is a widely applied method in sports science. Most performance evaluations focus on oxygen uptake parameters. Despite the well-established concept of oxygen deficit introduced by Hill in the 1920s, relatively few studies have examined its behavior during submaximal exercise, with limited exploration of deficit dynamics. The present study aimed to analyze the behavior of oxygen deficit in young female handball players (N = 42, age: 15.4 ± 1.3 years) during graded exercise. Oxygen deficit was estimated using the American College of Sports Medicine (ACSM) algorithm, restricted to subanaerobic threshold segments of a quasi-ramp exercise protocol. Cardiorespiratory parameters were measured with the spiroergometry test on treadmills, and body composition was assessed via Dual Energy X-ray Absorptiometry (DEXA). Cluster and principal component analyzes revealed two distinct athlete profiles with statistically significant differences in both morphological and physiological traits. Cluster 2 showed significantly higher relative VO2 peak (51.43 ± 3.70 vs. 45.70 ± 2.87 mL·kg-1·min-1; p < 0.001; Cohen`s d = 1.76), yet also exhibited a greater oxygen deficit per kilogram (39.03 ± 16.71 vs. 32.56 ± 14.33 mL·kg-1; p = 0.018; d = 0.80). Cluster 1 had higher absolute body mass (69.67 ± 8.13 vs. 59.66 ± 6.81 kg; p < 0.001), skeletal muscle mass (p < 0.001), and fat mass (p < 0.001), indicating that body composition strongly influenced oxygen deficit values. The observed differences in oxygen deficit profiles suggest a strong influence of genetic predispositions, particularly in cardiovascular and muscular oxygen utilization capacity. Age also emerged as a critical factor in determining the potential for adaptation. Oxygen deficit during submaximal exercise appears to be a multifactorial phenomenon shaped by structural and physiological traits. While certain influencing factors can be modified through training, others especially those of genetic origin pose inherent limitations. Early development of cardiorespiratory capacity may offer the most effective strategy for long-term optimization.